Lung cancer screening in Australia and New Zealand: the evidence and the challenge. Issue 3 (18th March 2021) - Manners, David; Dawkins, Paul; Pascoe, Diane; Crengle, Sue; Bartholomew, Karen; Leong, Tracy L.
Abstract: Lung cancer remains the commonest cause of cancer death in Australia and New Zealand. Targeted screening of individuals at highest risk of lung cancer aims to detect early stage disease, which may be amenable to potentially curative treatment. While current policy recommendations in Australia and New Zealand have acknowledged the efficacy of lung cancer screening in clinical trials, there has been no implementation of national programmes. With the recent release of findings from large international trials, the evidence and experience in lung cancer screening has broadened. This article discusses the latest evidence and implications for Australia and New Zealand.